2022
DOI: 10.3389/fimmu.2022.891147
|View full text |Cite
|
Sign up to set email alerts
|

A Protective HLA Extended Haplotype Outweighs the Major COVID-19 Risk Factor Inherited From Neanderthals in the Sardinian Population

Abstract: Sardinia has one of the lowest incidences of hospitalization and related mortality in Europe and yet a very high frequency of the Neanderthal risk locus variant on chromosome 3 (rs35044562), considered to be a major risk factor for a severe SARS-CoV-2 disease course. We evaluated 358 SARS-CoV-2 patients and 314 healthy Sardinian controls. One hundred and twenty patients were asymptomatic, 90 were pauci-symptomatic, 108 presented a moderate disease course and 40 were severely ill. All patients were analyzed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 52 publications
(63 reference statements)
1
10
0
Order By: Relevance
“…In previous studies, carried out during the outbreak of the SARS-CoV-2- B.1.1.7 variant in Italy, we observed how specific genetic factors in the Sardinian population significantly impact the outcome of COVID-19 infections ( 36 , 38 , 43 ). We have found that certain genetic factors, including the HLA extended haplotype HLA-B58:01, C07:01, DRB1*03:01, β°39 C>T variant at the HBB gene and KIR2DS2 gene/HLA C1 group ligand combination, can positively influence the course of the disease and result in an asymptomatic outcome ( 36 , 38 , 43 ).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…In previous studies, carried out during the outbreak of the SARS-CoV-2- B.1.1.7 variant in Italy, we observed how specific genetic factors in the Sardinian population significantly impact the outcome of COVID-19 infections ( 36 , 38 , 43 ). We have found that certain genetic factors, including the HLA extended haplotype HLA-B58:01, C07:01, DRB1*03:01, β°39 C>T variant at the HBB gene and KIR2DS2 gene/HLA C1 group ligand combination, can positively influence the course of the disease and result in an asymptomatic outcome ( 36 , 38 , 43 ).…”
Section: Introductionmentioning
confidence: 78%
“…We have found that certain genetic factors, including the HLA extended haplotype HLA-B58:01, C07:01, DRB1*03:01, β°39 C>T variant at the HBB gene and KIR2DS2 gene/HLA C1 group ligand combination, can positively influence the course of the disease and result in an asymptomatic outcome ( 36 , 38 , 43 ). While the Neanderthal-inherited haplotype ( rs35044562 , rs73064425 , rs34326463 , rs67959919 ) at the leucine zipper transcription factor-like 1 ( LZTFL1 ) has been associated with an increased risk of serious symptoms ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other recent studies illustrate the power of state-of-the-art genetics to reveal fundamentally new insights into immune system evolution [126] and large-scale human evolution in general [127]. Thus, a protective HLA extended haplotype was found to outweigh the major COVID-19 risk factor inherited from Neanderthals in the Sardinian population [126].…”
Section: Continuously Emerging New Levels Of Complexity Of the Human ...mentioning
confidence: 90%
“…Two other recent studies illustrate the power of state-of-the-art genetics to reveal fundamentally new insights into immune system evolution [126] and large-scale human evolution in general [127]. Thus, a protective HLA extended haplotype was found to outweigh the major COVID-19 risk factor inherited from Neanderthals in the Sardinian population [126]. Another large study [128] conducted multilocus genotyping of SARS-CoV-2 genomes sampled globally and found evidence the majority of SARS-CoV-2 infections in 2020 and 2021 caused by genetically distinct variants that likely adapted to local populations.…”
Section: Continuously Emerging New Levels Of Complexity Of the Human ...mentioning
confidence: 99%